American Muslims’ Anger and Sadness about In-group Social Image - Rodriguez Mosquera, Patricia M.; Khan, Tasmiha; Selya, Arielle (Frontiers in Psychology, 2017)
We present a novel study on the role of gender in perceptions of and emotions about in-group social image among American Muslims. Two hundred and five (147 females, 58 males) American Muslims completed a questionnaire on how Muslims feel in U.S. society. The study measured both stereotypical (i.e., ‘frightening,’ ‘oppressed’) as well as non-stereotypical in-group social images (i.e., ‘powerful,’ ‘honorable’). In particular, participants were asked how much they believe Muslims are seen as ‘frightening,’ ‘oppressed,’ ‘honorable,’ and ‘powerful’ in U.S. society, and how much anger and sadness they feel about the way U.S. society views Muslims. Participants believed Muslims are seen in stereotypical ways (i.e., as ‘frightening’ and ‘oppressed’) more than in non-stereotypical ways (i.e., as ‘powerful’ and ‘honorable’). Moreover, perceived in-group social image as ‘powerful’ or ‘honorable’ did not predict the intensity of felt anger or sadness. In contrast, the more participants believed Muslims are seen as ‘frightening,’ the more intense their anger and sadness. Furthermore, responses to perceived social image as ‘oppressed’ were moderated by gender. American Muslim female participants believed that Muslims are seen as ‘oppressed’ in U.S. society to a greater extent than male participants did. In addition, perceived social image as ‘oppressed’ only predicted anger for female participants: the more female participants believed Muslims are seen as ‘oppressed,’ the more intense their anger. This study contributes to the scarce literature on American Muslims in psychology, and shows that both anger and sadness are relevant to the study of perceived social image.